Dobre praktyki Wydziału Towaroznawstwa AE w Poznaniu (laureata Wielkopolskiej Nagrody Jakości 2007) w zarządzaniu kadrami - Foltynowicz, Zenon; Purol, Marta (Good Practices in Human Resources Management System Adopted by Faculty of Commodity Science, Poznan University of Economics - the Winner of Wielkopolska Quality Award in 2007, 2008)
In 2007 Faculty of Commodity Science, Poznan University of Economics (PCS, PUE), has been granted Wielkopolska Quality Award under the category of public organizations and institutions as a result of excellence in Total Quality Management. Beforehand, PCS took such improvement activities as: implementation and re-certification of the quality management system according to ISO 9001:2000 along with recognition by state and university commissions for accreditation. Good practices related to human resources management system have been established concerning motivation and professional development of employees. This article aims at presenting such good practices at PCS as: • promotion procedure, • motivation system, • teacher's evaluation system (student satisfaction survey, observations), • staff satisfaction survey, • setting of quality goals, evaluation of employees, internal communication. Effectiveness of the above mentioned practices has been confirmed by positive students' evaluations together with results of the PUE's Intellectual Capital Report. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 531-538